Acceptability of Child Adoption and adoption services among civil servants in Ibadan, Nigeria (2020)
Child adoption provides an opportunity for children to have new families and for parents to have children. Its acceptance by the society, however, may affect people’s decision to adopt. This study was conducted to determine the attitude and acceptability of child adoption and adoption services among 403 civil servants in Oyo State Secretariat, Ibadan in February and May, 2008.Self-administered questionnaire was used to collect data. Likert scale of score range 1-5 was used to measure respondents’ attitudes. Each positive attitude answer was given a score of 5, while each negative attitude answer had a score of 1. Total scores were computed for each respondent. Attitudinal scores within the range of 16-50 and 51-80 were considered negative and positive respectively. The mean age of respondents was 40.2 ± 9.7 years. Sixty five percent had tertiary education. Overall, 45.9% had positive attitude to adoption. A higher proportion of respondents who had tertiary education (56.3%) were supportive of adoption compared to the others. About 65.0% would support or encourage a relation to adopt a child while 68.5% would recommend adoption to a childless couple. Males, (57.2%), were more willing to support a relation who would like to adopt compared with females, (65.6%). The main reason for non-support of adoption by 32.4% of respondents was that they believed that the childless couples would have their biological children. Efforts should be made to improve the acceptability of adoption.